The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2009
DOI: 10.1111/j.1528-1167.2008.01914.x
|View full text |Cite
|
Sign up to set email alerts
|

Localized transmeningeal muscimol prevents neocortical seizures in rats and nonhuman primates: Therapeutic implications

Abstract: SUMMARYPurpose: To determine whether muscimol delivered epidurally or into the subarachnoid space can prevent and/or terminate acetylcholine (Ach)-induced focal neocortical seizures at concentrations not affecting behavior and background electroencephalography (EEG) activity. Methods: Rats (n = 12) and squirrel monkeys (n = 3) were chronically implanted with an epidural or subarachnoid drug delivery device, respectively, over the right frontal/parietal cortex, with adjacent EEG electrodes. Recordings were perf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
33
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
3
2
2

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(36 citation statements)
references
References 30 publications
3
33
0
Order By: Relevance
“…Unlike in rats, in monkeys, the subarachnoid strip or grid can be chronically implanted in the subarachnoid space. We showed that with such a device the epidural pharmacological data obtained in rats can be replicated in primates: subdural/subarachnoid muscimol completely prevented focal, acetylcholine (Ach)-induced neocortical seizures in monkeys in a concentration well tolerated by the animals (Ludvig et al, 2009). Fig.…”
Section: Supporting Experimental Datamentioning
confidence: 97%
See 3 more Smart Citations
“…Unlike in rats, in monkeys, the subarachnoid strip or grid can be chronically implanted in the subarachnoid space. We showed that with such a device the epidural pharmacological data obtained in rats can be replicated in primates: subdural/subarachnoid muscimol completely prevented focal, acetylcholine (Ach)-induced neocortical seizures in monkeys in a concentration well tolerated by the animals (Ludvig et al, 2009). Fig.…”
Section: Supporting Experimental Datamentioning
confidence: 97%
“…Thus, epidurally administered diazepam, pentobarbital and muscimol have been shown to prevent and/or terminate experimentally induced focal neocortical seizures in rats (Collins, 1980;Eder et al, 1997;Stein et al, 2000;Ludvig et al, 2006Ludvig et al, , 2009. Relevant autoradiographic and histological studies have demonstrated the actual intracortical diffusion and spread of water-soluble drugs, such as acetylcholine, N-methyl-D-aspartate and methylene blue (Cornblath and Ferguson, 1976;Ludvig et al, 2008).…”
Section: Supporting Experimental Datamentioning
confidence: 99%
See 2 more Smart Citations
“…Recent advances in biomedical engineering leads the way to many exciting implantable devices for neural signal recording and processing [1]- [4] and drug delivery [5]. As the implantable devices get more complicated to include more functionality, their power requirements also increase.…”
Section: Introductionmentioning
confidence: 99%